2020
DOI: 10.1155/2020/8881683
|View full text |Cite
|
Sign up to set email alerts
|

Literature‐Based Drug Repurposing in Traditional Chinese Medicine: Reduced Inflammatory M1 Macrophage Polarization by Jisil Haebaek Gyeji‐Tang Alleviates Cardiovascular Disease In Vitro and Ex Vivo

Abstract: Relatively high proportions of proinflammatory M1-like macrophages in tissues may lead to vascular impairment and trigger numerous diseases including atherosclerosis-related cardiovascular disease (CVD). Jisil Haebaek Gyeji-tang (JHGT), a polyherbal decoction, is traditionally used to treat various human ailments including chest pain, angina, and myocardial infarction. In the present study, we investigated the anti-inflammatory effects of JHGT on lipopolysaccharide- (LPS-) stimulated M1 macrophage polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…In addition to NF-κB and JNK signaling, the activation of p44/42 MAPK and Akt signaling was observed to regulate the transcription of pro-inflammatory cytokines in macrophages. Indeed, it has been reported that a wide variety of herbal extracts and herbderived natural compounds exert anti-inflammatory effects on LPS-stimulated macrophage cell lines, such as RAW264.7 and U937, by suppressing either p44/42 MAPK signaling [37][38][39][40] or Akt signaling [41][42][43]. In this regard, we found that ETAS®50 co-treatment suppressed S1-induced phosphorylation of p44/42 MAPK and Akt after 6 h of culture.…”
Section: Discussionmentioning
confidence: 49%
“…In addition to NF-κB and JNK signaling, the activation of p44/42 MAPK and Akt signaling was observed to regulate the transcription of pro-inflammatory cytokines in macrophages. Indeed, it has been reported that a wide variety of herbal extracts and herbderived natural compounds exert anti-inflammatory effects on LPS-stimulated macrophage cell lines, such as RAW264.7 and U937, by suppressing either p44/42 MAPK signaling [37][38][39][40] or Akt signaling [41][42][43]. In this regard, we found that ETAS®50 co-treatment suppressed S1-induced phosphorylation of p44/42 MAPK and Akt after 6 h of culture.…”
Section: Discussionmentioning
confidence: 49%
“…In addition to NF-κB and JNK signaling, the activation of p44/42 MAPK and Akt signaling was observed to regulate the transcription of pro-inflammatory cytokines in macrophages. Indeed, it has been reported that a wide variety of herbal extracts and herb-derived natural compounds exert anti-inflammatory effects on LPS-stimulated macrophage cell lines, such as RAW264.7 and U937, by suppressing either p44/42 MAPK signaling [ 35 , 36 , 37 , 38 ] or Akt signaling [ 39 , 40 , 41 ]. In this regard, we found that EAS co-treatment suppressed S1-induced phosphorylation of p44/42 MAPK and Akt after 6 h of culture without affecting the degradation of IκBα degradation and nuclear translocation of NF-κB p65 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…RAW264.7 cells were seeded and grown at 37°C and 5% CO 2 for 24 h. RAW264.7 cells were cultured in 1 μg/mL dexamethasone (Sigma, United States), 10–300 μg/mL PLE and 500 ng/mL lipopolysaccharide (LPS) for 24 h. Then, cell supernatants were mixed with Griess reagent (1:1 ratio), and the NO concentration was measured at 540 nm ( Lee et al, 2019 ; Jo et al, 2020 ). Cell viability was analyzed using Ez-Cytox reagent (DoGenBio, Korea) according to the manufacturer’s protocols ( Yu et al, 2020 ; Jo et al, 2023a ). This experiment was repeated triplicated.…”
Section: Methodsmentioning
confidence: 99%